2012
DOI: 10.1111/j.1399-0004.2012.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of neonatal diabetes and monogenic syndromic diabetes in Asian Indian children

Abstract: Mutations in the pancreatic ATP sensitive K(+) channel proteins [sulfonyluea receptor 1 (SUR1) and inward rectifier K(+) channel Kir6.2 (Kir6.2), encoded by ATP-binding cassette transporter subfamily C member 8 (ABCC8) and potassium channel J11 (KCNJ11), respectively], are the most common cause of neonatal diabetes. We describe the clinical presentation and molecular characterization of Asian Indian children with neonatal diabetes mellitus and monogenic syndromes of diabetes. We sequenced KCNJ11, ABCC8 and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Here, we describe the structural and functional cause of heterozygous SUR1 ( ABCC8, NM_000352.4) mutations in five different genetically unrelated Asian Indian children associated with NDM or with some neurological features. Of the five mutations characterized in this study, two (D212Y and R653Q) have been previously reported by our group . The P254S mutation has been reported in an Indian patient by Flanagan et al The R992C and Q1224H mutations have not been reported in Asian Indian children so far.…”
Section: Introductionsupporting
confidence: 49%
“…Here, we describe the structural and functional cause of heterozygous SUR1 ( ABCC8, NM_000352.4) mutations in five different genetically unrelated Asian Indian children associated with NDM or with some neurological features. Of the five mutations characterized in this study, two (D212Y and R653Q) have been previously reported by our group . The P254S mutation has been reported in an Indian patient by Flanagan et al The R992C and Q1224H mutations have not been reported in Asian Indian children so far.…”
Section: Introductionsupporting
confidence: 49%
“…In contrast to the western literature, Indian literature shows that Transient neonatal diabetes accounts only for 5% of all neonatal diabetes mellitus [5,6]. Chromosome 6q related mutations followed by ABCC8 (SUR) mutations and KCNJ11 account for most of TNDM.…”
Section: Discussionmentioning
confidence: 64%
“…Though transient in about 50% of children, diabetes recurs in the pediatric age group or in the early adult age group. Children in remission need to be followed up annually for hyperglycemia [6].…”
Section: Discussionmentioning
confidence: 99%
“…This is an excellent illustration of precision diabetes and one of the most exciting clinical situations in diabetology. Switching a child aged just a few weeks or months to oral tablets, from what would otherwise have meant lifelong insulin injections, is nothing short of a miracle to the child and the family, and we have been able to help many such children [50]. …”
Section: Monogenic Diabetes: the Field Where Precision Diabetes Has Amentioning
confidence: 99%